Pengaruh Latihan Target Shooting Drill Terhadap Akurasi Shooting dalam Permainan Futsal - Ariel Eko Saputra; Rizal Ahmad Fauzi; Adang Sudrazat (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine the effect of target shooting drill training on the improvement of players’ shooting accuracy in futsal games. The research method used was pre-experimental with a One Group Pretest-Posttest Design. The population of this study was futsal players of Khairamah Futsal Academy. The sampling technique used purposive sampling, obtaining 30 male futsal players aged 11–16 years as the research sample. The test instrument used was a shooting accuracy test with a goal target. Based on the descriptive analysis results, there was an increase in the average shooting accuracy score of the players from 7.00 at pre-test to 16.90 at post-test. The Wilcoxon Signed Rank Test results showed a Z value of -4.788 with a significance value of Asymp. Sig. (2-tailed) of 0.000 (p < 0.05). The conclusion of this study is that target shooting drill training has a significant effect on the improvement of futsal players’ shooting accuracy. Keywords: Futsal, Shooting Accuracy, Target Shooting Drill, Training